On Estimates of the Kolmogorov Widths of the Classes B_p,θ^r in the Space L_q - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain an order estimate for the Kolmogorov width of the Besov classes B_p,θ ^r of periodic functions of many variables in the space L_q for 2 < p < q < ∞, which complements the result obtained earlier by the author.